Exploiting heterogeneous environments: does photosynthetic acclimation optimize carbon gain in fluctuating light? - Retkute, Renata (Oxford University Press, 2015)

(untitled)
We propose a new mathematical model to empirically determine how successful plants are at maximizing daily carbon gain in fluctuating light according to dynamic acclimatory processes.